2018
DOI: 10.1021/acsnano.8b01341
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Increase in Polymer Glass Transition Temperature under Extreme Nanoconfinement in Weakly Interacting Nanoparticle Films

Abstract: Properties of polymers in polymer nanocomposites and nanopores have been shown to deviate from their respective bulk properties due to physical confinement as well as polymer-particle interfacial interactions. However, separating the confinement effects from the interfacial effects under extreme nanoconfinement is experimentally challenging. Capillary rise infiltration enables polymer infiltration into nanoparticle (NP) packings, thereby confining polymers within extremely small pores and dramatically increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 84 publications
9
85
0
Order By: Relevance
“…The results obtained here complement previous studies of homopolymers in hard confinement, where a substantial increase in the local T g was observed by covalently bonding (grafting) polymer chains to a solid substrate vs. simply coating the polymer onto the same weakly-interacting substrate [32][33][34], or when the polymer layer being probed rests atop a grafted brush layer attached to a hard substrate [35][36][37]. The present study highlights the utility of fluorescence labeling and temperature-dependent spectroscopy, which provide component-specific measurements of T g , to probe features of the glass transition in complex polymer systems.…”
Section: Main Textsupporting
confidence: 85%
“…The results obtained here complement previous studies of homopolymers in hard confinement, where a substantial increase in the local T g was observed by covalently bonding (grafting) polymer chains to a solid substrate vs. simply coating the polymer onto the same weakly-interacting substrate [32][33][34], or when the polymer layer being probed rests atop a grafted brush layer attached to a hard substrate [35][36][37]. The present study highlights the utility of fluorescence labeling and temperature-dependent spectroscopy, which provide component-specific measurements of T g , to probe features of the glass transition in complex polymer systems.…”
Section: Main Textsupporting
confidence: 85%
“…The glass transition temperature increases for the composite material, as shown by the TanDelta (calculated as the ratio between storage and loss moduli) (Figure 8B) and confirmed in the DSC (Supplementary Figure S10). The T g increase is most likely partially because of nanoparticles in high concentration [55]. In fact, as mentioned above, the chain end of the polymer would be hindered by the particles and would have difficulties vibrating during the DMA experiment.…”
Section: Thermomechanical Properties Of Pmpsmentioning
confidence: 96%
“…Similarly, Priestley and coworkers showed that aging in polymer nanoparticles is significantly varied if the nature of the confinement is hard or soft . Polymers infiltrated into packed inorganic nanoparticles exhibit significant differences in behavior compared to the supported film, which further illustrates the importance of the local environment on the physical properties of confined polymers . These results have implications in a variety of applications where thin films of polymers are utilized, especially for membrane separations …”
Section: Introductionmentioning
confidence: 95%